Investigation on the performance and characteristics of a heat pump system for electric vehicles under extreme temperature conditions. (October 2021) - Li, Kang; Luo, Shuxian; Fan, Le; Hu, Shasha; Zhou, Xuejin; Tu, Ran; Zhang, Huiqi; Jin, Xiaotang; Zhao, Xiaoshan; Su, Lin
Abstract: The driving ranges of electric vehicles (EVs) will decrease greatly with increased use of the vehicle heating system in a cold climate. Air conditioning heat pump (ACHP) systems, which convert energy stored in the ambient environment into heat, represent a promising approach for increasing the EV driving range. In this work, the performance of an ACHP system in an EV under extremely cold conditions is investigated experimentally. The requirements of an ACHP system for EVs at various ambient temperatures are determined using our capacity matching strategy. A prototype system designed based on these requirements is evaluated. Data collected from experiments performed at a full-scale facility under extreme temperature conditions are analyzed. The results show that the ACHP system proposed for EV applications can satisfy both the cooling and heating requirements for the passenger compartment. The system increased the driving range by 23% when compared with that of an EV using a positive-temperature-coefficient (PTC) heater at −10 °C. Highlights: ● Performance characteristics of an electric vehicle ACHP system designed were studied. ● System accuracy was enhanced using both experimental and theoretical data. ● Air outlet temperature performance in a car compartment was studied systematically. ● The influence of heating methods on EV driving range was evaluated.